Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am using this sum:

$$\sum_{k=1}^\infty \frac{(-1)^{k-1}}{k}\left((-1)^{k-1} (n-1) + \sum_{j=1}^{k-1}\frac{(-1)^{j+k-1}n (\log n)^j}{j!}\right)$$

Empirically, this is precisely equal to

$$\sum_{k=1}^\infty \frac{(\log n)^k}{k! k}$$

which is the most significant term in this expansion of the logarithmic integral

$$\operatorname{li}(n) = \log \log n + \gamma + \sum_{k=1}^\infty \frac{(\log n)^k}{k! k}$$

where $\gamma$ is the Euler-Mascheroni constant.

Can anyone show why my sum is equal to the sum from the logarithmic integral?

share|cite|improve this question
Where you wrote $-1^{k-1}$, I am guessing you meant $(-1)^{k-1}$ and I changed it to that. – Michael Hardy Sep 12 '11 at 18:30
Note that when you write \log x rather than log x, then the backslash not only prevents "log" from being italicized, but it also provides proper spacing, so you don't need the spacing you did manually. – Michael Hardy Sep 12 '11 at 18:31
All of the $(-1)^{k-1}$ cancel out and there's only a $(-1)^j$ left in on the right numerator. – Henning Makholm Sep 12 '11 at 18:33
Michael - Thanks. I'm still getting used to Latex and MathJax. – Nathan McKenzie Sep 12 '11 at 19:39
Henning: True. The reason I kept the terms in its original, unnecessarily messy form, is that what I'm really trying to show is the relationship I've written up at . Basically, it's a way of using Linnik's identity to connect the prime counting function to the logarithmic integral. I can get from the prime counting function up to the sum I just posted, but this last jump is stumping me. – Nathan McKenzie Sep 12 '11 at 19:40
up vote 5 down vote accepted

I'll start the same way as Sasha, except that I'll first replace $n$ with $\exp\,z$:


From here, we recall that the partial sums of the exponential function possess the following integral representation (see here for a proof):

$$\exp(-u)\sum_{j=0}^{k-1}\frac{u^j}{j!}=\frac1{(k-1)!}\int_u^\infty t^{k-1} \exp(-t)\mathrm dt$$

so we make the replacement:

$$-\frac1{k}+\frac1{k!}\int_{-z}^\infty t^{k-1} \exp(-t)\mathrm dt$$

Let's complicate things a bit:

$$-\frac{(k-1)!}{k!}+\frac1{k!}\int_{-z}^\infty t^{k-1} \exp(-t)\mathrm dt$$

and replace $(k-1)!=\Gamma(k)$ with its integral representation:

$$\frac1{k!}\left(-\int_0^\infty t^{k-1} \exp(-t)\mathrm dt+\int_{-z}^\infty t^{k-1} \exp(-t)\mathrm dt\right)$$

which simplifies:

$$\frac1{k!}\int_{-z}^0 t^{k-1} \exp(-t)\mathrm dt$$

We now treat the sum

$$\sum_{k=1}^\infty \frac1{k!}\int_{-z}^0 t^{k-1} \exp(-t)\mathrm dt$$

and swap summation and integration (justification left to the reader):

$$\int_{-z}^0\left(\sum_{k=1}^\infty \frac{t^{k-1}}{k!}\right)\exp(-t)\mathrm dt$$

which becomes

$$\int_{-z}^0\left(\frac{\exp\,t-1}{t}\right)\exp(-t)\mathrm dt=\int_{-z}^0\frac{1-\exp(-t)}{t}\mathrm dt=-\int_z^0\frac{1-\exp\,t}{-t}\mathrm dt=\int_0^z\frac{\exp\,t-1}{t}\mathrm dt$$

and since

$$\int_0^z\frac{\exp\,t-1}{t}\mathrm dt=\sum_{j=1}^\infty \frac{z^j}{j! j}$$

the claim is proven.

share|cite|improve this answer
Wow. Thanks. Great to see that proven. – Nathan McKenzie Sep 13 '11 at 10:20
@Nathan: You're welcome. I haven't peered at how you implemented the computation of the logarithmic integral in your web page, but just in case: you might be interested in Ramanujan's series for the logarithmic integral (formula 15 here); I've found it slightly more efficient than the straightforward series for medium-sized arguments. – J. M. Sep 13 '11 at 10:23
The series I provided is even slower than Formula 14 from that page. Instead, its interest to me is from the following (this is my argument from my webpage - I'll try to go quick): If you have the strict divisor functions $d_1(n) = 1$ and $d_k(n) = \sum_{j | n, 1 < j < n}d_1(j)d_{k-1}(n/j)$, then Linnik's identity says $\sum_{k=1} (-1^{k+1})/k \cdot d_k(n) = $1/a if n = $p^a$ where p is a prime, 0 otherwise. Sum this from 2 to n, and you have $\sum_{j=2}^n 1 - 1/2\sum_{j=2}^n \sum_{k=2}^{n/j} 1+ 1/3\sum_{j=2}^n \sum_{k=2}^{n/j}\sum_{l=2}^{n/(jk)} 1 - ... = \Pi(n)$ – Nathan McKenzie Sep 13 '11 at 11:33
The term on the right is the prime power counting function. Approximate the sums on the left as $\int_{1}^n dx - 1/2\int_{1}^n \int_{1}^{n/x} dydx+ 1/3\int_{1}^n \int_{1}^{n/x}\int_{1}^{n/xy} dz dy dx - ...$, evaluate these integrals, and you immediately have the sums I asked about. I knew empirically that my integrals here were equal to $li(x) - \log \log x - \gamma$, but... – Nathan McKenzie Sep 13 '11 at 11:33
I see, @Nathan. I do have to agree that those are cute-looking multiple integrals... :) – J. M. Sep 13 '11 at 11:40

First of all note that the term being added to the inner sum can be absorbed into the sum as follows:

$$ (-1)^{k-1} (n-1) + \sum_{j=1}^{k-1} (-1)^{j+k-1} n \frac{\log^j n}{j!} = (-1)^k \left( 1 - \sum_{j=0}^{k-1} (-1)^{j} n \frac{\log^j n}{j!} \right) $$ Now, write $1 = \sum_{j=0}^{\infty} (-1)^{j} n \frac{\log^j n}{j!}$. Thus the original sum becomes

$$ \mathcal{S} = \sum_{k=1}^\infty \frac{1}{k} \sum_{j=k}^{\infty} (-1)^{j} n \frac{\log^j n}{j!} $$ Now exchange the order of summation $\sum_{k=1}^\infty \sum_{j=k}^\infty \to \sum_{j=1}^\infty \sum_{k=1}^{j}$: $$ \mathcal{S} = \sum_{j=1}^\infty \sum_{k=1}^{j} \frac{1}{k} (-1)^{j} n \frac{\log^j n}{j!} = n \sum_{j=1}^\infty (-1)^{j} H_j \frac{\log^j n}{j!} $$

I am not sure at the spot how to manually convert this into logarithmic integral function, but Mathematica can solve this sum in terms of LogIntegral[n]:

n Sum[(-1)^j HarmonicNumber[j] Log[n]^j/j!, {j, 1, Infinity}] == 
    Log[Log[n]] + EulerGamma - LogIntegral[n] // FullSimplify[#, n > 1] &

Out[179]= True
share|cite|improve this answer
Is exchanging the order of infinite sums sound when the terms have different signs? It's not clear to me that the double sum converges absolutely. – Henning Makholm Sep 12 '11 at 19:09
The exchange can be carried out with the upper summation bound fixed at $m$, and later $m$ would be sent to infinity: $\sum_{k=1}^m \sum_{j=k}^m \to \sum_{j=1}^m \sum_{k=1}^{j}$ – Sasha Sep 12 '11 at 19:21
But is it valid to go from $\sum_{k=1}^{\infty}\sum_{j=k}^{\infty}$ to $\lim_{m\to\infty}\sum_{k=1}^m \sum_{j=k}^{m}$ in the first place? – Henning Makholm Sep 12 '11 at 19:25
Regarding that last sum: I suspect manipulations similar to what Srivatsan did here might be useful. In particular, I ended up with the integral $$\int_0^1 \frac{\exp(-zt)-\exp(-z)}{t-1}\mathrm dt$$ after trying it out myself. – J. M. Sep 13 '11 at 10:43

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.